Ilustração e natureza: uma história ambiental no Maranhão setecentista? (1773-1790) - MONTEIRO, Alessandra Cristina Costa (2017)
This research seeks to know the introduction of scientific practices in the Captaincy of Maranhão in the second half of the 18th century in the context of Natural History of Portugal. In the opportunity, to think the relations of the man with the nature from the study of the shipments of natural sorts sent from Maranhão to Europe, is between the preoccupations. It matters: What elements of nature were being sent? To what extent did the local nature meet the needs of the Natural History of Portugal? Was there an Enlightenment project for Maranhão? Is it possible to identify environmental impacts arising from the exploitation of these natural resources? These are some of the main questions that guide the research presented here. In order to do so, we are guided in the methods of investigation of Environmental History and use as source the correspondence exchanged between the governors of the Captaincy of Maranhão and the Secretary of State for Marine and Overseas Business, Martinho de Melo e Castro in the period of 1773 to 1790.